Structural and biochemical insights into the role of the nucleosome in transcriptional activation in yeast - White, Cindy LuAnn Holland, author; Luger, Karolin, advisor; Stargell, Laurie A., committee member; Peersen, Olve, committee member; Laybourn, Paul J., committee member; Anderson, Oren P., committee member (Colorado State University. Libraries, 2003)
In vivo transcription occurs in the context of highly compacted chromatin. The fundamental repeating element in chromatin and the primary level of DNA compaction is the nucleosome core particle, which comprises 147 base pairs of DNA wrapped around a histone octamer. The extreme compaction of DNA found in the confines of the nucleus has profound implications for our understanding of transcription regulation, since chromatin must allow transcriptional access to specific regions of the DNA molecule while keeping the remaining regions repressed. Approaching these problems by using yeast as a model organism, we determined the three-dimensional structures of the macromolecular complexes in question, and studied nucleosomal dynamics using biochemical and biophysical methods. First, we solved the crystal structure of the nucleosome core particle from the yeast Saccharomyces cerevisiae. Compared to higher eukayotes, the structure of the yeast nucleosome suggests a less stable structure, as well as a mechanism for looser nucleosomal compaction, since yeast nucleosome crystals demonstrate an altered packing within the crystal lattice. Biophysical analysis of the stability of yeast nucleosomes confirmed that they are less stable compared to those of Xenopus laevis. We then investigated the role of poly (dA-dT) DNA sequence elements, found in many yeast promoter regions, on transcriptional activation within a nucleosome context. Our results suggest that these rigid DNA tracts form nucleosomes with the same affinity as a strong positioning DNA sequence, and the formed nucleosome is not destabilized by the presence of the poly (dA-dT) tract. We also find that these elements create areas of greater nucleosomal DNA accessibility, which leads to a more efficient binding of a transcription factor. Finally, we show that a transcription factor can bind directly to nucleosomal DNA near the dyad causing partial dissociation of the DNA ends, but does not bring about the dissociation of the underlying histone octamer. Taken together, these studies shed light on the interactions between transcription factors and nucleosomes, and thus allow us to better analyze the interplay between chromatin packaging and transcriptional regulation at the molecular level.
Keywords: biochemistry; molecular biology